Dominica : Staff Report for the 1999 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2000)
Economic growth averaged about 2.5 percent a year in the 1990s, and the structure of the economy continued to move away from agriculture as the key banana sector contracted further. Broad money has continued to grow at a slightly higher rate than nominal GDP. At the same time, commercial banks expanded credit to the private sector at a fast pace during 1998-99. Executive Directors welcomed the authorities' plan to broaden the tax base by replacing a number of indirect taxes with a value-added tax.